2009
DOI: 10.1021/je900320r
|View full text |Cite
|
Sign up to set email alerts
|

Re-Evaluation of the Thermodynamic Activity Quantities in Aqueous Rubidium and Cesium Chloride Solutions at 25 °C

Abstract: The Hückel equation used in this study to correlate the experimental activities of dilute RbCl and CsCl solutions up to a molality of about 3.5 mol·kg−1 contains two parameters being dependent on the electrolyte: B [that is related closely to the ion-size parameter (a*) in the Debye−Hückel equation] and b 1 (this parameter is the coefficient of the linear term with respect to the molality, and this coefficient is related to hydration numbers of the ions of the electrolyte). In more concentrated solutions up … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
68
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 30 publications
(70 citation statements)
references
References 24 publications
(157 reference statements)
2
68
0
Order By: Relevance
“…In the previous studies, it was found that the following Hückel equations apply very well to the thermodynamic properties of NaCl [11], KCl [11], LiCl [19], RbCl [20], CsCl [20], and alkali metal bromide [21] solutions at least up to a molality of 1 mol Á kg À1 :…”
Section: Theorymentioning
confidence: 89%
See 4 more Smart Citations
“…In the previous studies, it was found that the following Hückel equations apply very well to the thermodynamic properties of NaCl [11], KCl [11], LiCl [19], RbCl [20], CsCl [20], and alkali metal bromide [21] solutions at least up to a molality of 1 mol Á kg À1 :…”
Section: Theorymentioning
confidence: 89%
“…In more concentrated solutions, the following extended Hückel equations were used here as earlier [11,[18][19][20][21] for the activity and osmotic coefficients:…”
Section: Theorymentioning
confidence: 99%
See 3 more Smart Citations